Who are patients classified within the new terminology of heart failure from the 2016 ESC guidelines?. (31st January 2017) - Delepaul, Benoit; Robin, Guillaume; Delmas, Clément; Moine, Thomas; Blanc, Adrien; Fournier, Pauline; Roger‐Rollé, Aénora; Domain, Guillaume; Delon, Clémence; Uzan, Charles; Boudjellil, Rabah; Carrié, Didier; et al.
Abstract: Aims: The main terminology used to describe heart failure (HF) is based on measurement of the left ventricular ejection fraction (LVEF). LVEF in the range of 40–49% was recently defined as HF with mid‐range EF (HFmrEF) by the 2016 European Society of Cardiology guidelines. The purpose of our study was to assess the clinical profile and prognosis of patients with HF according to this new classification. Methods and results: A total of 482 patients referred for HF were retrospectively included over a period of 1 year. There were 258 (53%), 115 (24%), and 109 (23%) patients with HF with reduced EF (HFrEF), HFmrEF, and HF with preserved EF (HFpEF), respectively. Patient age increased, whereas left block bundle branch, brain natriuretic peptide level, and the use of beta‐blocker and furosemide decreased from HFrEF to HFpEF. After adjustment for the age, patients with HFpEF and HFmrEF were more likely to have NYHA stage 2 dyspnea, had a higher systolic blood pressure, were less likely to have spironolactone, had lower furosemide dose, and had lower haemoglobin than those with HFrEF. Cardiovascular risk factors and medical history were similar in the three groups of patients. There was a 33% death rate after a mean follow‐up of 32.2 ± 14.3 months. The survival was the same among patients whatever the group of HF ( P = 0.884). Conclusions: Patients with HFrEF, HFmrEF, and HFpEF share the same cardiovascular risk factors, medical history, and prognosis. Patients with HFmrEF have a different clinical profile, which is nearly the same as patients with HFpEF, except for sex. These results question the relevance of this new classification of HF to stimulate research into this new group of patients.